MENAKAR KONTRIBUSI ISLAMIC BRANDING, PERSONAL SALLING, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HIJAB PASHMINA - Handayani, Nurul; Jauhariyah, Nur Anim; Aniati, Ana (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to examine and analyze the effect of Islamic branding, personal selling, and product quality simultaneously on the purchasing decision of Pashmina Hijab at Pondok Pesantren Darussalam Blokagung Banyuwangi. Quantitative approach by distributing questionnaires to 100 respondents was done randomly and then analyzed using multiple regression. The results of the analysis show that Islamic branding, personal selling, and product quality simultaneously have a significant and positive effect on the purchasing decisions of Pashmina Hijab made by female students at Pondok Pesantren Darussalam Blokagung Banyuwangi with a contribution of 67.5%.